2003
DOI: 10.7182/prtr.13.1.e6w229973t37141g
|View full text |Cite
|
Sign up to set email alerts
|

Presumed consent and other predictors of cadaveric organ donation in Europe

Abstract: Findings may be useful to academics and professionals responsible for organ procurement. Additional research is necessary for practical application of findings. Generalizing these findings beyond Europe may be problematic because of external validity constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 9 publications
1
30
0
1
Order By: Relevance
“…Whereas there are no differences across years, there is a strong effect of the default: When donation is the default, there is a significant increase in donation, increasing from 14.1 to 16.4, a 16.3% increase. Using similar techniques, but looking only at 1999 for a broader set of countries, another similar study reports an increase from 10.8 to 16.9, a 56.5% increase (Gimbel et al, 2003).…”
Section: S18mentioning
confidence: 97%
See 1 more Smart Citation
“…Whereas there are no differences across years, there is a strong effect of the default: When donation is the default, there is a significant increase in donation, increasing from 14.1 to 16.4, a 16.3% increase. Using similar techniques, but looking only at 1999 for a broader set of countries, another similar study reports an increase from 10.8 to 16.9, a 56.5% increase (Gimbel et al, 2003).…”
Section: S18mentioning
confidence: 97%
“…We examined the actual number of caderveric donations made per million on a slightly larger list of countries between 1991 and 2001, controlling for variables known to affect donation rates (see Gimbel, Strosberg, Lehrman, Gefenas, & Taft, 2003). Whereas there are no differences across years, there is a strong effect of the default: When donation is the default, there is a significant increase in donation, increasing from 14.1 to 16.4, a 16.3% increase.…”
Section: S18mentioning
confidence: 99%
“…3,4 Various factors have been implicated to influence the donation rate, including the presence of presumed consent system, level of public awareness and education, number of transplant programs or organisations available in the community, donor factors, next-of-kin factors, religious view, and others. [4][5][6][7][8][9][10] Although presumed consent is not currently available in the UK (except Wales), it has been shown that presumed consent practice alone is not sufficient to resolve the shortage of organ and tissue donation. 11 Geissler et al 12 suggested that improved eye donation coordination network could enhance eye donation rate, including comprehensive review of all hospital deaths and use of a well-defined protocol.…”
Section: Introductionmentioning
confidence: 99%
“…This is clearly above the EU average of 17.8 per million population. (English, 2007;Wright, 2007), religion and religious beliefs (Gimbel et al, 2003;Rumsey et al, 2003), the efficiency of a country's transplant co-ordination (Johnson & Goldstein, 2004); GPD and health expenditure per capita (Healy, 2005), awareness of organ donation (Oz et al, 2003), blood donation rate (Abadie & Gay, 2006), knowledge of someone who had donated an organ after death and awareness of any one who received a donated organ (Rumsey et al, 2003), education (Gimbel et al, 2003), and attitudes towards organ donation and presumed consent (Roels et al, 1997).…”
Section: Is Opting-out the Solution?mentioning
confidence: 99%